Associations Between Developmental Stability, Canalization, and Phenotypic Plasticity in Response to Heterogeneous Experience - Shu Wang; Ragan M. Callaway (Ecology and Evolution)
ABSTRACT The processes of developmental stability, canalization, and phenotypic plasticity have ecological and evolutionary significance, and been studied extensively, but mostly separately and thus the relationships between them are not straightforward. Our objective was to better integrate these processes in the context of temporally heterogeneous environments. We did this by investigating the effects of early experience with temporal heterogeneity in water availability on associations between developmental stability, canalization, and phenotypic plasticity. We subjected eight plant species to a first round of alternating inundation and drought vs. constantly moderate water treatments (heterogeneous experience) and a second round of water conditions (to test plasticity). We measured fluctuating asymmetry (FA) in leaf size, intra‐ and inter‐individual variation (CVintra and CVinter), and plasticity (PI) in traits and analyzed correlations between these variables across all species. Results showed little correlations between FA, CVintra and PI, several positive correlations between FA and CVinter in more stressful conditions, especially in as well as positive correlations between CVinter and PI initially and negative correlations between them later. These suggested the complexity of these relationships, which can depend on whether plasticity occurs. Greater inter‐individual variation will more likely cooperate with plasticity before or during plastic response, whereas higher canalization may reflect phenotypic convergence. Both higher FA and CVintra can reflect faster growth, while CVintra may also reflect plant growth stage, and the two mechanisms should cooperate in response to environmental challenges. The complexity of these relationships suggests plants deal with environmental variation in elaborate and integrative ways which can be affected by many factors.